Catalytic Asymmetric Piancatelli Rearrangement: Brønsted Acid Catalyzed 4π Electrocyclization for the Synthesis of Multisubstituted Cyclopentenones. Issue 45 (10th October 2016) - Cai, Yunfei; Tang, Yurong; Atodiresei, Iuliana; Rueping, Magnus
Abstract: The first catalytic asymmetric Piancatelli reaction is reported. Catalyzed by a chiral Brønsted acid, the rearrangement of a wide range of furylcarbinols with a series of aniline derivatives provides valuable aminocyclopentenones in high yields as well as excellent enantioselectivities and diastereoselectivities. The high value of the aza‐Piancatelli rearrangement was demonstrated by the synthesis of a cyclopentane‐based hNK1 antagonist analogue. Abstract : A chiral Brønsted acid catalyzes the asymmetric Piancatelli rearrangement of a wide range of furylcarbinols with aniline derivatives, affording valuable 4‐aminocyclopentenones in high yields and with high enantio‐ and diastereocontrol. Challenging alkyl‐substituted tertiary furylcarbinols gave the corresponding products with a chiral quaternary stereocenter with excellent enantioselectivity.